Sosialisasi Circular Economy Dengan Pemanfaatan Limbah UMKM Coffee Shop “Nostalgia0254” Menjadi Sabun Scrub Natural - Setyo Rini, Asih (LPPM ITEBA, 2026)
Daily operations of coffee shop MSMEs generate a considerable amount of coffee grounds waste, which is generally discarded without further utilization. However, coffee grounds still possess physical characteristics and natural compounds that allow them to be processed into value-added products, such as natural scrub materials. This study aims to design a natural scrub soap product utilizing coffee grounds waste from “Nostalgia0254” Coffee Shop MSME. The Quality Function Deployment (QFD) method was applied to translate customer needs into technical product specifications through the House of Quality (HoQ). The results indicate that natural ingredient composition, soap pH level, and coffee grounds concentration are the main technical priorities. This product design is expected to support waste reduction initiatives and enhance the sustainable economic value of MSMEs.